Researching mobile-assisted Chinese-character learning strategies among adult distance learners. Issue 1 (2nd January 2018) - Qian, Kan; Owen, Nathaniel; Bax, Stephen
ABSTRACT: In the field of teaching and learning Chinese as a foreign language (CFL), most studies investigate Chinese character learning strategies in pen-and-paper study by campus-based students. With the increase in distance-learning, and expanding popularity of smartphones and tablets and widespread availability of mobile applications for language learning, it is now important to research mobile-assisted character learning strategies by distance learners. This study attempts to (i) identify changing practices when character learning is assisted by mobile technology; and (ii) analyse the underlying causes for the changing practices. These issues were investigated using an online survey, learning diary and email interviews with UK-based distance learners of beginners' Chinese ( n = 22). The findings suggest that there are important emerging new practices and previously unreported strategies such as constantly testing oneself and using pinyin input to identify new characters. They also reveal two strategy types not reported in previous research concerning social and affective dimensions. The study thereby provides important new insights into how adult distance learners of Chinese at beginners' level learn characters when assisted by mobile technology, with significant pedagogical implications for Chinese character pedagogy in terms of course design and learner support.